Smaller Inguinal Hernias are Independent Risk Factors for Developing Chronic Postoperative Inguinal Pain (CPIP): A Registry-based Multivariable Analysis of 57, 999 Patients. Issue 4 (April 2020) - Hoffmann, Henry; Walther, Daniela; Bittner, Reinhard; Köckerling, Ferdinand; Adolf, Daniela; Kirchhoff, Philipp
Abstract : Objective: Impact of inguinal hernia defect size as stratified by the European Hernia Society (EHS) classification I to III on the rate of chronic postoperative inguinal pain (CPIP). Background: CPIP is the most important complication after inguinal hernia repair. The impact of hernia defect size according to the EHS classification on CPIP is unknown. Methods: In total, 57, 999 male patients from the Herniamed registry undergoing primary unilateral inguinal hernia repair including a 1-year follow-up were selected between September 1, 2009 and November 30, 2016. Using multivariable analysis, the impact of EHS inguinal hernia classification (EHS I vs EHS II vs EHS III and/or scrotal) on developing CPIP was investigated. Results: Multivariable analysis revealed for smaller inguinal hernias a significant higher rate of pain at rest [EHS I vs EHS II: odds ratio, OR = 1.350 (1.180–1.543), P < 0.001; EHS I vs EHS III and/or scrotal: OR = 1.839 (1.504–2.249), P < 0.001; EHS II vs EHS III and/or scrotal: OR = 1.363 (1.125–1.650), P = 0.002], pain on exertion [EHS I vs EHS II: OR = 1.342 (1.223–1.473), P < 0.001; EHS I vs EHS III and/or scrotal: OR = 2.002 (1.727–2.321), P < 0.001; EHS II vs EHS III and/or scrotal: OR = 1.492 (1.296; 1.717), P < 0.001], and pain requiring treatment [EHS I vs EHS II: OR = 1.594 (1.357–1.874), P < 0.001; EHS I vs EHS III and/or scrotal: OR = 2.254 (1.774–2.865), P < 0.001; EHS II vs EHS III and/or scrotal: OR = 1.414 (1.121–1.783), P = 0.003] at 1-year follow-up. Younger patients (<55 y) revealed higher rates of pain at rest, pain on exertion, and pain requiring treatment (each P < 0.001) with a significantly trend toward higher rates of pain in smaller hernias. Conclusions: Smaller inguinal hernias have been identified as an independent patient-related risk factor for developing CPIP.